Regulation of Finance and Accounting 21st and 22nd Virtual Annual Conference on Finance and Accounting (ACFA2020-21), Prague, Czech Republic - Procházka, David (Springer Proceedings in Business and Economics, 2022)
X, 471 p. 73 illus., 36 illus. in color.